(untitled) (Revista Contexto & Educação, 2023)
With the aim of provoking reflections on consumption behaviors, the educational product was a proposal for curse of Initial and Continuing Formation (FIC) of Consumer Habits, applied in the context of Integrated High School (EMI) to Professional and Technological Education (EPT). The course proposal was applied at the IFRN Campus Ipanguaçu from conversation circles with generating themes, with data collection for the research through the application of questionnaires, direct observation and the reviews of the discussions in the conversation circles that the students produced at the end of each meeting, after the application of the product, an evaluation was carried out by the participants. Therefore, the result was positive, as the students realized that knowing how the decision-making process takes place in the human mind will contribute to their financial education, as well as the aforementioned Consumption Habits Training course contains elements that enable the replication of the action. in educational contexts in general.